Dielectric properties of ultraviolet cured poly(dimethyl siloxane) sub-percolative composites containing percolative amounts of multi-walled carbon nanotubes1. Issue 17 (27th February 2015) - Goswami, K.; Daugaard, A. E.; Skov, A. L.
<x xml:space="preserve">Abstract</x> Novel preparation scheme allows for heterogeneous distributions of conductive filler such that percolative amounts can be added without obtaining percolative properties.